Identification of new genetic resources for drought tolerance-related traits from the world Erianthus germplasm collection - Ramanathan, Valarmathi; Pradhan, Anjan Kumar; Gandham, Prasad; Chinnaswamy, Appunu; Mahadeva Swamy, H. K.; Mohanraj, K.; R, Rasitha; Baisakh, Niranjan (Frontiers in Plant Science, 2025)
Drought is one of the most complex abiotic stress factors and significantly affects sugarcane production worldwide. With an objective to identify drought-tolerant wild sugarcane germplasm for sugarcane improvement, a set of 223 diverse Erianthus clones collected from seven different countries were assessed for drought tolerance-related traits at the formative stage. A drought association panel of 91 Erianthus clones with differential drought response was developed for genomic studies to identify marker–trait associations. Drought-tolerant Erianthus clones maintained high chlorophyll fluorescence (Fv/Fm) and relative water content and chlorophyll content, and were able to regulate photosynthetic rate as well as canopy cooling to sustain growth and biomass accumulation. They also recorded high stress tolerance indices and a low susceptibility index. Moderate to high heritability estimates of the traits suggested that the traits were under genetic control. A genome-wide association study conducted using 1,044 genotyping by sequencing-derived high-quality single-nucleotide polymorphism markers on the drought panel identified 43 quantitative trait nucleotides (QTNs) associated with various physiological traits that explained phenotypic variance ranging from 0.26% to 59.35%. Candidate genes [Target of Rapamycin 2 (TOR2), Trans-Membrane Kinase 1 (TMK1), potassium transporter auxin response factor, FAD-binding PCMH-type domain-containing protein, and Nitrate Transporter 1/Peptide Transporter Family (NRT1/PTR)] involved in drought perception and signaling were successfully identified in QTN regions. The present study identified drought-tolerant Erianthus clones and the QTNs associated with drought tolerance traits for further validation and subsequent utilization in the sugarcane breeding program.